Saccharide isomerate ameliorates cosmetic scalp conditions in a Chinese study population. (11th April 2022) - Martin, Emmanuel; Zhang, Anson; Campiche, Remo
Abstract: Background: Scalp conditions such as flaky or oily scalp affect people across ethnicities and age groups. In addition to flaking, increased sebum secretion, itching, and compromised scalp barrier function were described. Scalp conditions are aesthetically disturbing and may cause psychological distress in affected individuals who are looking for mild and effective treatment at the same time. Saccharide isomerate has a long history as a skin moisturizer, and it was found to improve skin barrier function, also suggesting possible beneficial effects on scalp. Aims: To provide relevant claim substantiation to introduce saccharide isomerate as a new scalp care active against scalp flaking condition. Material and Methods: We conducted a placebo‐controlled clinical study in an adult Chinese population affected by dandruff scalp as assessed by an adherent scalp flaking score. We monitored transepidermal water loss (TEWL), sebum secretion, and scalp flaking during 28 days. Results: Formulations containing Saccharide isomerate significantly improved all parameters both over time as well as compared to the placebo formulation. Conclusion: We propose Saccharide isomerate for cosmetic formulations directed toward improving scalp conditions such as dandruff or oily scalp.